The revolutions of written culture. Dialogue and interventions - González del Riego, Delfina (2005)
Roger Chartier is perhaps one of the most renowned French historians in the field of cultural history today. He has dedicated a large part of his career to investigating the history of private life and, particularly, the world of books, publishers and readers. His historiographic concern has focused on the study of writing-reading practices, the modes of production of what is written (from papyrus to codex, from book to screen), and the appropriation and reconstruction of meanings by readers in the different times.